2017
DOI: 10.11648/j.jfns.20170504.11
|View full text |Cite
|
Sign up to set email alerts
|

Physico Chemical, Antioxidant and Pasting Properties of Pre-heated Purple Sweet Potato Flour

Abstract: Purple sweet potatoes contain anthocyanins which could function as a natural food colorant, and an antioxidant.One of the problems in handling the fresh roots is their susceptibility during storage, and to extend their uses, fresh purple sweet potato could be processed into flour. However, during flouring process, the properties of the purple sweet potato may undergo some changes such as partial gelatinization of the starch and discolorization. Therefore, the purpose of this study was to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
12
0
4
Order By: Relevance
“…[40] This may be due to the differences in the native granule architecture and fragility. [53] Their results were in line with Nurdjanah et al [54] who found that the native sweet potato flour contains starch granule which is round, spherical and surrounded by cell wall material (Figure 3). Ndangui et al [3] studied the impact of thermal and chemical pretreatments on physicochemical, rheological, and functional properties of sweet flour and they observed composed of smooth, round, and spherical granules with quite irregular that exhibits dents .…”
Section: Morphological Propertiessupporting
confidence: 82%
See 2 more Smart Citations
“…[40] This may be due to the differences in the native granule architecture and fragility. [53] Their results were in line with Nurdjanah et al [54] who found that the native sweet potato flour contains starch granule which is round, spherical and surrounded by cell wall material (Figure 3). Ndangui et al [3] studied the impact of thermal and chemical pretreatments on physicochemical, rheological, and functional properties of sweet flour and they observed composed of smooth, round, and spherical granules with quite irregular that exhibits dents .…”
Section: Morphological Propertiessupporting
confidence: 82%
“…[53] The granule size is reported to affect some functional properties and physiology function. [37,54] Wide variability in the size and shape of starch granules has been observed (Figures 3 and 4). Scanning electron microscopy has played an important role in increasing understanding of the granular structure of modified flour starches and used to detect structural changes caused by chemical modifications and the most substituted regions in starch granules.…”
Section: Morphological Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Tepung ubi jalar ungu yang telah dimodifikasi secara fisik menggunakan panas dilaporkan dapat memperbaiki sifat fungsional, kadar air tepung yang lebih rendah dari pada kadar air tepung control serta dapat mempertahankan warna aslinya 28,29 .…”
Section: Pendahuluanunclassified
“…However, this sweet potato consists of several types, while the most common type is white, yellow, orange and purple-fleshed sweet potato. However, purple sweet potato is still less known than any other types, although the antocyanin content of this type is considered high and becoming a source of natural antioxydant which can be beneficial for our body (Nurdjanah et al, 2017). Antocyanin content of purple sweet potato is relatively high, which is up to 519 mg/100gr of the wet weight.…”
Section: Introductionmentioning
confidence: 99%